PENGELOLAAN RETRIBUSI PASAR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH KOTA SURAKARTA TAHUN ANGGARAN 2018-2022 - Putri, Tara Yuniar; Suhita, Damayanti; Winduro, Wirid (Master of Public Administration, Universitas Slamet Riyadi, 2024)
This research aims to describe the management of Surakarta City market retribution in increasing Surakarta City's Regional Original Revenue (PAD) for the 2018-2022 fiscal year. The method used in this research is a descriptive method using a qualitative approach with several sources of informants from the Surakarta City Trade Office, the Head of the Surakarta City Market and several market traders in Surakarta City. Data collection techniques using observation, interview, and documentation methods. Data analysis techniques used are data collection, data condensation, data presentation, and verification/conclusion drawing. The result of the research concludes that the management of market levy in increasing Local Revenue of Surakarta City is good, it is seen from some dimensions of indicators developed by George R Terry (1958) in Sukana (2011:10). From the Planning aspect, the management of market levy in Surakarta City is good, it can be seen from the existence of clear objectives, structured management steps and appropriate retribution revenue targets. From the Organizing aspect, it is also good, proven by the existence of appropriate division of labor, as well as the cooperation between several parties. From the aspect of Actuating, the management of market retribution in Surakarta City is good, this is seen from the existence of clear implementation methods and structured work processes. From the Controlling aspect, it is good, it is proven by the supervision on the work implementation process, the evaluation and problem solving conducted by the agency directly. However, there are several things that must be considered by the Trade Office related to the method of payment of market retribution, and the target of market retribution revenue. Keywords: Management, Local Revenue, Market Retribution.